PLANTS USED BY AFRICAN TRADITIONAL HEALERS IN THE MANAGEMENT OF ORAL DISEASES: A REVIEW - Agbor, Ashu Michael; Naidoo, Sudeshni (International Journal of Research -GRANTHAALAYAH, 2019)
Background: Plants form the basis of African traditional medicine which has contributed to significantly to the reduction of mortality, morbidity and disability due to many diseases. Medicinal plants have been reported to be an essential aspect oral health delivery cutting across all facets of oral health care. Method: Publications and reports on the use of African traditional medicine in oral health care were reviewed from published scientific journals, books, reports from national, regional and international organizations, research theses, conference papers and other grey material. International online databases such as MEDLINE, Science Direct, Scopus and Google were also searched up to 2015. Publications were limited to the English and French language Results: This review identified medicinal plant use by traditional healers in preventive, therapeutic and surgical aspects in the oral health and also identified some research gaps which further studies should be carried out. Conclusion: Medicinal plants has enormous benefits in the management of oral diseases but faces some challenges like toxicity, processing and follow-ups. Research on medicinal plants use in African traditional medicine in oral health is still scanty and most often incomplete.